Modeling 3D garments by examples - Li, Jituo; Lu, Guodong (Computer aided design, 2014)
3D garments are created by assembling 2D patterns on human models in current mainstream garment modeling methods, which usually calls for professional design skills. The high coupling between the 2D pattern making and 3D garment design blocks the designers’ creations. In this paper, a novel approach that decouples the high coupling between garment design and pattern making is proposed. Our approach is examples based. 3D new garment models are created on individual human models by compositing 3D parts from garment examples rather than 2D patterns. The main benefit of our approach is that it is easy to operate and capable to create elegant individualized garments with highly detailed geometries. Garment prototypes represented in Coons surface automatically generated from individual human models are used to guide the garment parts composition and locally parameterize the garment parts. With the local parameterization, the garment parts and the newly created garment models can be interactively edited by altering the parametric curves on the garment prototypes. Our approach makes it possible for both the designers and the common customers to express their creations and imaginations conveniently in a 3D graphical way. [Display omitted] •Designing 3D garments by directly compositing 3D parts from existing examples.•Decoupling the high coupling between garment design and pattern making.•The first attempt for examples-based 3D garment modeling.